Gamma, neutron shielding and mechanical parameters for lead vanadate glasses. Issue 11 (1st August 2019) - Mahmoud, I.S.; Issa, Shams A.M.; Saddeek, Yasser B.; Tekin, H.O.; Kilicoglu, Ozge; Alharbi, T.; Sayyed, M.I.; Erguzel, T.T.; Elsaman, Reda
Abstract: Alkali lead vanadate glasses with moderate concentrations of PbO were prepared and analyzed to test their use as promising candidates for radiation shielding. The physical parameters of these glasses are specified and discussed in details. The code MCNPX was utilized to determine the mass attenuation coefficient μm that is used to evaluate the interaction of radiation with shielding materials. The results were then compared with the values collected from the XMuDat program and XCOM. The simulation results overlaps and highly correlated with XMuDat and XCOM. In addition, the results showed that μm, the effective atomic number (Zeff ), removal cross-sections, (ΣR ) and experimental results of the prepared glasses increase, while the half value layer (HVL), exposure and energy absorption build-up factor (EBF and EABF) values decrease with the increase of lead oxide (PbO) content from 30 to 45 mol%. In order to maximize the benefits from the determination of the radiation factors, the experimentally determined physical parameters and the elastic coefficients of this type of glass were also calculated.